KERAHASIAAN BANK SEBAGAI WUJUD PERLINDUNGAN HUKUM TERHADAP NASABAH PENYIMPAN DANA DIKAITKAN DENGAN MONEY LAUNDERING - Prim Hadi Susetya, I Gde; Puspawati, I Gusti Ayu; Putu Sutama, Ida Bagus (Kertha Negara : Journal Ilmu Hukum; Vol. 01, no. 01, Maret 2013)
One function of banks is to collect funds from the public, so that people want to save their money, it takes confidence to the bank with one of the bank's actions to maintain bank secrecy. People who become customers of a bank must perform actions such as making financial transactions. The problem that then arises is whether the depositor gets the transfer of more than Rp. 100,000,000, will be protected from the bank and how the application of sanctions against violations of bank secrecy? Depositors are protected confidentiality if they do not deal suspicious financial transactions; it is associated with money laundering. A bank liability is reported that if found indications money laundering. As for the application of sanctions against violators of bank secrecy will be conducted by Bank Indonesia after conducting in-depth examination of the report of a violation of bank secrecy. Therefore, the protection of bank secrecy laws does not apply if depositors do money laundering and the imposition of sanctions against offenders classified by Bank Indonesia after inspection. Therefore, it is expected the bank to find out all that was done by the customer to prevent money laundering. The application of sanctions has been running well but needs to improve again in supervision.
Keywords: bank secrecy, money laundering, suspicious transaction, imposition of sanction